Replication Data for: Ihle-Soto, Costoya et al. ... - Bacigalupo, Antonella; Ihle-Soto, Camila; Costoya, Eduardo; Correa, Juana P.; Cornejo-Villar, Berenice; Estadella, Viviana; Solari, Aldo; Ortiz, Sylvia; Hernández, Héctor J.; Botto-Mahan, Carezza; Gorla, David E.; Cattan, Pedro E. (Harvard Dataverse, 2019)
Small mammals and triatomines data regarding infection by Trypanosoma cruzi, DTUs and captures time and place. Summer and winter 2011; Región de Coquimbo (Localities 1 and 2), Región de Valparaíso (Localities 3 and 4), and Región Metropolitana (Localities 5 and 6), CHILE. ...